A Coordinative Solubilizer Method to Fabricate Soft Porous Materials from Insoluble Metal–Organic Polyhedra1. Issue 19 (2nd April 2019) - Carné‐Sánchez, Arnau; Craig, Gavin A.; Larpent, Patrick; Guillerm, Vincent; Urayama, Kenji; Maspoch, Daniel; Furukawa, Shuhei
Abstract: Porous molecular cages have a characteristic processability arising from their solubility, which allows their incorporation into porous materials. Attaining solubility often requires covalently bound functional groups that are unnecessary for porosity and which ultimately occupy free volume in the materials, decreasing their surface areas. Here, a method is described that takes advantage of the coordination bonds in metal–organic polyhedra (MOPs) to render insoluble MOPs soluble by reversibly attaching an alkyl‐functionalized ligand. We then use the newly soluble MOPs as monomers for supramolecular polymerization reactions, obtaining permanently porous, amorphous polymers with the shape of colloids and gels, which display increased gas uptake in comparison with materials made with covalently functionalized MOPs. Abstract : By reversibly attaching bulky ligands to the axial coordination sites of insoluble metal paddlewheels, metal–organic polyhedra can be dissolved and incorporated into microporous polymers via supramolecular polymerization reactions.